SELF ORGANIOZING FUZZY CONTROLLER FOR A NONLINEAR TIME VARYING SYSTEM (Journal of Engineering, 2006)
This paper proposes a self organizing fuzzy controller as an enhancement level of the fuzzy controller. The adjustment mechanism provides explicit adaptation to tune and update the position of the output membership functions of the fuzzy controller. Simulation results show that this controller is capable of controlling a non-linear time varying system so that the performance of the system improves so as to reach the desired state in a less number of samples.